Analysis of Factors that Affect Employee Work Accidents at PT. Windu Blambangan Sejati (WBS) Banyuwangi Regency 2018 - Ruri Firmansyah; Sismulyanto Sismulyanto; Nurwijayanti Nurwijayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Workplaces always have various hazard factors that can affect the health of the workforce or can cause work-related disorders or illnesses. Accidents, the essence is an unexpected event and certainly not expected by anyone. These unexpected events, obviously not a form of intentional and not planned in advance. Accidents arise as a result of managing potential hazards and risks to low occupational safety and health. The purpose of the study was to analyze the factors that influence employee work accidents at PT. Windu Blambangan Sejati (WBS) Banyuwangi Regency. The research design used was cross sectional. The research population is all employees of PT. Windu Blambangan Sejati (WBS) Banyuwangi Regency and a large sample of 81 people using simple random sampling. Data collection using questionnaire sheets was then analyzed using logistic regression tests. The results showed that there was an influence of skills on workplace accidents (p-value = 0.027 <0.05). There is an influence of experience on workplace accidents (p-value = 0.043 <0.05). There is an influence of discipline on workplace accidents (p-value = 0.040 <0.05). There is an influence of Technical factors (availability of equipment) on workplace accidents (p-value = 0.003 <0.05). There is no effect of lay out on work accidents (p-value = 0.420> 0.05). There is no effect of lighting on work accidents (p-value = 0.944> 0.05). There is no noise effect on work accidents (p-value = 0.084> 0.05). Based on these studies, company management pays more attention to these three factors, namely human, technical and environmental by conducting periodic and periodic maintenance